2023
DOI: 10.1177/10775595231167320
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Differences in Child Protective Services Reporting, Substantiation and Placement, With Comparison to Non-CPS Risks and Outcomes: 2005–2019

Abstract: We used National Child Abuse and Neglect Data System and Census data to examine Black–White and Hispanic–White disparities in reporting, substantiation, and out-of-home placement both descriptively from 2005–2019 and in multivariate models from 2007–2017. We also tracked contemporaneous social risk (e.g., child poverty) and child harm (e.g., infant mortality) disparities using non-child protective services (CPS) sources and compared them to CPS reporting rate disparities. Black–White CPS reporting disparities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Indeed, after analyses control for sociodemographic variables, Black newborns exposed to illicit drugs appear less likely to be reported than White newborns. Similarly, others found that racial disproportionality in CPS’ overall statistics is largely confounded by poverty, with further support by a recent analysis . Reported Black children were less likely to have maltreatment substantiated and less likely to be placed out of home than White children .…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Indeed, after analyses control for sociodemographic variables, Black newborns exposed to illicit drugs appear less likely to be reported than White newborns. Similarly, others found that racial disproportionality in CPS’ overall statistics is largely confounded by poverty, with further support by a recent analysis . Reported Black children were less likely to have maltreatment substantiated and less likely to be placed out of home than White children .…”
mentioning
confidence: 79%
“…Similarly, others found that racial disproportionality in CPS' overall statistics is largely confounded by poverty, 5 with further support by a recent analysis. 6 Reported Black children were less likely to have maltreatment substantiated and less likely to be placed out of home than White children. 6 Clearly, child poverty and its many associated burdens are strongly linked to a lengthy list of problems.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Roberts, 2022). Available data do not support these common assumptions (Barth et al, 2021;Drake et al, 2023). Since 2018, black children are slightly less likely to be substantiated than white children (Children's Bureau, 2023a, tab.…”
Section: Abolition Positionmentioning
confidence: 99%
“…Black parents' greater racial identification was associated with lower child abuse risk and less observed negative parenting, whereas the reverse was true for White parents. In another study using the National Child Abuse and Neglect Data System and U.S. Census data, Drake et al (2023) examined Black-White and Latine-White disparities in reporting, substantiation, and home removal, controlling for social risk (e.g., child poverty) and child harm (e.g., infant mortality) disparities using non-child protective services (CPS) sources to unravel confounding in CPS data. They found Black-White and Latine-White CPS reporting disparities were lower than disparities in non-CPS risk benchmarks.…”
Section: In This Issuementioning
confidence: 99%